Social Space Construction of Spirit’s Isan - Potiwan, Piyaluk (Journal of Cultural Approach, 2016)
This article is an attempt to reflect the system spiritualism context of Isan base on why the belief persists amid a cultural change and this faith is important in the adoption of social control. This study used qualitative research methods, data collection in the Northeast region (Isan) through understanding and study of spiritualism and the process of creating a social space. The result found; the Isan communities have spiritualism through pass on and processes of socialization that expressed in the form of traditions and rituals. The goal was to express gratitude, the prosperity of the joy of living, including a mechanism of social control.